THE IMPACT OF MEDIA ON CULTURE: ACASE STUDY OF SALT TELEVISION IN RUBAGA DIVISION KAMPALA DISTRICT - Nassozi Hudah (Uganda Christian University, 2024)
This study examined “the effects of media on culture using Salt TV as a case study located in Kampala City's Rubaga Division.” Thirteen parishes were included in the study: Busega, Lubaga, Lugala, Namirembe, Kasubi, Kawala, Mutundwe, Nateete, Ndeeba, Kabowa, Najjanankumbi, Lungujja, and Kawala. Through an analysis of media consumption trends, cultural transformations, and interpersonal relationships among parishioners, the study sought to determine the ways in which Salt TV affected regional cultural dynamics. Surveys, interviews, and content analysis were used in the data collection process to get information from locals and media sources. Significant cultural effects linked to Salt TV were found, including modifications to social norms, community involvement, and cultural behaviors. The study emphasized how media plays a significant role in forming cultural identity and promoting social cohesiveness in Rubaga. The study found that Salt TV had both beneficial and detrimental effects on Rubaga Division's cultural fabric. The enhancement of regional customs and the creation of a forum for cross-cultural communication and expression were two positive effects. On the other hand, detrimental outcomes like cultural homogenization and the possible deterioration of traditional values were observed. These results highlight the intricate connection between culture and media, pointing to the necessity of a reasonable approach to media regulation and consumption in order to protect cultural heritage while embracing modernity.